1997
DOI: 10.1002/(sici)1096-9861(19970310)379:2<185::aid-cne2>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Mesopontine organization of cholinergic and catecholaminergic cell groups in the normal and narcoleptic dog

Abstract: Canine narcolepsy is a unique experimental model of a human sleep disorder characterized by excessive daytime sleepiness and cataplexy. There is a consensus recognition of an imbalance between cholinergic and catecholaminergic systems in narcolepsy although the underlying mechanisms remain poorly understood. Possible substrates could be an abnormal organization, numbers and/or ratio of cholinergic to catecholaminergic cells in the brain of narcoleptic dogs. Therefore, we sought to characterize the correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 63 publications
4
17
0
Order By: Relevance
“…According to previous reports, the A9 ventral subdivision of the substantia nigra is lacking in carnivores (Tafti et al, 1997), and although reported in the hedgehog, the existence of this group is uncertain since it is represented by a very small number of neurons (Michaloudi and Papadopoulos, 1996). The A9 ventral subdivision has been seen in monotremes, opossum, artiodactyls, dolphin, rodents, tree shrews and primates (Crutcher and Humbertson, 1978;Dahlström and Fuxe, 1964;Hökfelt et al, 1984;Manger et al, 2002bManger et al, , 2004Murray et al, 1982;Østergaard et al, 1992;Tillet and Kitahama, 1998).…”
Section: Catecholaminergic Systemsupporting
confidence: 86%
“…According to previous reports, the A9 ventral subdivision of the substantia nigra is lacking in carnivores (Tafti et al, 1997), and although reported in the hedgehog, the existence of this group is uncertain since it is represented by a very small number of neurons (Michaloudi and Papadopoulos, 1996). The A9 ventral subdivision has been seen in monotremes, opossum, artiodactyls, dolphin, rodents, tree shrews and primates (Crutcher and Humbertson, 1978;Dahlström and Fuxe, 1964;Hökfelt et al, 1984;Manger et al, 2002bManger et al, , 2004Murray et al, 1982;Østergaard et al, 1992;Tillet and Kitahama, 1998).…”
Section: Catecholaminergic Systemsupporting
confidence: 86%
“…Presence of nucleus indicated by '+', absence by 'À', and unknown by '?'. Data taken from: Manger et al (2002b), Crutcher and Humbertson (1978), Michaloudi and Papadopoulos (1996), Maseko and Manger (2007), Østergaard et al (1992), Ruggiero et al (1992), Leshin et al (1995), Tillet and Kitahama (1998), Tillet and Thibault (1989), Manger et al (2003Manger et al ( , 2004, Dahlström and Fuxe (1964), Armstrong et al (1982), Hökfelt et al (1984), Greater canerat (Dwarika, Maseko, Ihunwo, Fuxe, Manger, personal observation), Moon et al (2007), Da Silva et al (2006), Blessing et al (1978), Cheung and Sladek (1975), Poitras and Parent (1978), Reiner and Vincent (1987), Kitahama et al (1990), Henderson (1987), Dormer et al (1993), Tafti et al (1997), Murray et al (1982), Jacobowitz and MacLean (1978), Felten et al (1974), Hubbard and Di Carlo (1974a), Lavoie and Parent (1994), Garver and Sladek (1975), Schofield and Everitt (1981), Satoh and Fibiger (1985), Bogerts (1981), Pearson et al (1983), Halliday et al (1988), Kitahama et al (1996). medullary tegmentum has been reported for monotremes, rats, cats and ferrets (Armstrong et al, 1982Henderson, 1987;Shiromani et al, 1988;<...>…”
Section: Cholinergic Systemmentioning
confidence: 85%
“…A medullary tegmental field was not found in the megabat studied. This loose aggregation of cholinergic neurons in the Karasawa et al (2003), Dinopoulos et al (1988), Maseko and Manger (2007), Ferreira et al (2001), Armstrong et al (1983), Tago et al (1989), Da Silva et al (2006), Kimura et al (1981), Vincent and Reiner (1987), Shiromani et al (1988), Henderson (1987), Tafti et al (1997), St-Jacques et al (1996), Everitt et al (1988), Lavoie and Parent (1994), Mesulam et al (1984), Kus et al (2003), Satoh and Fibiger (1985), Mizukawa et al (1986), Mesulam et al (1989). Presence of nucleus indicated by '+', absence by 'À', and unknown by '?'.…”
Section: Cholinergic Systemmentioning
confidence: 99%
“…Somatostatin-positive perikarya have been found in the retrorubral area of the cat and the rat by some authors (Graybiel and Elde 1983;Vincent et al 1985) but not others (Johansson et al 1984;Spangler and Morley 1987). In the dog, labeled cells in this area overlap the ventral extension of the A8 dopaminergic neuronal group that have been suggested to play a key role in the progression of the Parkinson's disease (Arts et al 1996;Tafti et al 1997;García et al 1997). The dense population of labeled cells in the rostral part of the dorsal raphe nucleus of the dog closely resembles a similar population described in the rat (Johansson et al 1984).…”
Section: Discussionmentioning
confidence: 99%